Long-term curing impact on properties, mineral composition and microstructure of hemp shive-cement composite. (10th November 2018) - Balčiūnas, Giedrius; Pundienė, Ina; Boris, Renata; Kairytė, Agnė; Žvironaitė, Jadvyga; Gargasas, Justinas
Highilights: Mechanical properties of composite during long-term hardening period increase. Changes of properties are caused by continuing hydration and carbonation procesess. Hydration and carbonisation depends from Al2 (SO4 )3 and Ca(OH)2 ratio with cement. Qualitative analysis of the composite composition is conducted using X-ray and DTA. Abstract: Fibre Hemp Shiv (FHS) is one of the most widely used bio-aggregates for the development of eco-friendly building materials. Research on composites with an FHS aggregate has usually been limited to short-term property analyses that depend on the type of binder. Such properties are determined after (7–90) days of curing. Most scientists have focused on researching composites with lime (L) based binders. This work focuses on composites with a cement (CEM) binder and FHS aggregate, and investigates the impact of long-term curing (for 1 year) on the physical properties (density, compressive strength and thermal conductivity) of composites with non-treated and mineralized FHS (mineralization is performed with aluminium sulphate (AS) and hydrated lime (L)). In order to determine the causes of the changes in properties during long-term curing, changes in the mineralogical composition are analysed. X-ray diffraction, differential thermal and thermogravimetric analyses as well as research on the microstructure of the composites are implemented. The lowest change in properties due to inhibition of hydration is determined for composites with a non-treated aggregate. Mineralized aggregates are characterized by lower cement hydration capability over a long-term period. The change of properties after 1 year of curing depends on the AS/CEM ratio. For all 1-year cured composites, there is a reduction in the peak intensities of C2 S, C3 S and ettringite, whereas there is an increase in the peak intensities of calcite, (except for composition with the highest AS/CEM ratio – AS30L18), Calcium Silicate Hydrate (CSH) and portlandite (except for the non-mineralized composition). Lower ratios for AS/CEM (AS18L36 and AS21L42) and, respectively, higher L/CEM ratios in compositions lead to the formation of vaterite. In addition, the above-mentioned composition has the highest L/CEM ratio, which ensures that more hydrates participate in the carbonation process, thus leading to higher compressive strength, denser composite structure and higher thermal conductivity due to higher heat transfer by conduction.